Bilanggo life as a political prisoner in the Philippines, 1952-1962 - Pomeroy, William J. 1916- (Quezon City University of the Philippines Press, 2009)
"Bilanggo is the diary of a decade behind bars. William Pomeroy and his Filipina wife Celia Mariano, like hundreds of other communists and militants, were sent to prison in the early 1950s for participating in the Huk guerilla struggle for liberation... Although this is the story of political prisoners in Philippine jails some fifty years ago, it is a story that has increasing relevance in a society that has seen increased political oppression in the last decade."--Back cover.
Manila court of first instance, June 18, 1952 -- Camp Murphy, July-August 1952 -- The road to Muntinglupa, August 1952 -- Muntinglupa, 1952, 1953, 1954 -- Camp Panopio, 1954 -- Muntinglupa, 1955-56, 1957, 1958 -- Fort McKinley, 1958-59, 1960-61 -- Engineers Island -- Epilogue.
Keywords: Pomeroy, William J. -- 1916-.; Political prisoners -- Philippines -- Biography